2023
DOI: 10.3389/fpls.2022.1098751
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and proteomic analyses provide insights into host adaptation of a bamboo-feeding aphid

Abstract: IntroductionSalivary glands and their secreted proteins play an important role in the feeding process of sap-sucking aphids. The determination of saliva composition is an important step in understanding host plant adaptation of aphids. Pseudoregma bambucicola is a severe bamboo pest in subtropical areas and the only aphid species that can exclusively feed on hard stalks of bamboos. How this species can penetrate and degrade hard bamboo cell walls and utilize a very specialized niche are important unanswered qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Aphids, to avoid plant toxic metabolites, utilize detoxification enzymes, primarily cytochrome P450, esterase, carboxypeptidase, and glutathione peroxidase, in their saliva and these enzymes are known in this study. These detoxification enzymes were commonly reported in insects, including aphids (Bos et al, 2010;Rao et al, 2013;Thorpe et al, 2017;Zhang et al, 2023), hoppers (Hattori et al, 2015;Liu et al, 2016), whiteflies (Su et al, 2012;Huang et al, 2020), thrips (Stafford-Banks et al, 2014), and psyllids (Wu et al, 2021). The trehalse enzyme has been detected in the proteome of cowpea aphids and has also been documented in the salivary glands of numerous insects (Nicholson et al, 2012;Liu et al, 2016;Yu and Killiny, 2018;Zhang et al, 2023).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Aphids, to avoid plant toxic metabolites, utilize detoxification enzymes, primarily cytochrome P450, esterase, carboxypeptidase, and glutathione peroxidase, in their saliva and these enzymes are known in this study. These detoxification enzymes were commonly reported in insects, including aphids (Bos et al, 2010;Rao et al, 2013;Thorpe et al, 2017;Zhang et al, 2023), hoppers (Hattori et al, 2015;Liu et al, 2016), whiteflies (Su et al, 2012;Huang et al, 2020), thrips (Stafford-Banks et al, 2014), and psyllids (Wu et al, 2021). The trehalse enzyme has been detected in the proteome of cowpea aphids and has also been documented in the salivary glands of numerous insects (Nicholson et al, 2012;Liu et al, 2016;Yu and Killiny, 2018;Zhang et al, 2023).…”
Section: Resultsmentioning
confidence: 89%
“…Some of these potential effectors have functions known as pectinases, glucanases, or amylases involved in the degradation of the wall of plant cells. Other potentially secreted proteins have detoxification functions such as metalloproteases, oxidoreductases, peroxidases, or phenol oxidases (Rao et al, 2013;Thorpe et al, 2016;Zhang et al, 2017;Zhang et al, 2023). The cowpea aphid, Aphis craccivora Koch (Hemiptera: Aphididae), is an important legume pest and poses a severe threat to agriculture causing yield losses of up to 40% and also transmits harmful plant pathogenic viruses, including cowpea aphid-borne mosaic virus and others (Blackman and Eastop, 2000;Boukar et al, 2016).…”
mentioning
confidence: 99%
“…All insects in our study, and especially aphid species, harbor Buchnera , which plays a crucial role in providing nutrition. Previous studies reported that P. bambusicola loses its ability to feed on Bambusa , so their symbiotic bacteria help them to receive nutrition [ 75 ]. Treponema was only detected in termites ( Figure 2 B), which help them to degrade cellulose.…”
Section: Discussionmentioning
confidence: 99%